Dinamika Interaksi Agama dan Tradisi Lokal: Analisis Kehadiran Gereja Katolik dan Adat Masyarakat Kutai Lawas Kedang Ipil - Paulinus Siringoringo (Perspektif, 2026)
This article aims to analyze the dynamics of the encounter between the Kutai Lawas Kedang Ipil customary law (adat) and the presence of the Catholic Church, specifically within the context of pastoral care and faith inculturation. The Kutai Lawas community is known for possessing a strong customary system, rich in noble values such as reverence for ancestors, communal solidarity, and the sacredness of the relationship with nature. These values form the foundation of the local community's social and spiritual life. The arrival of the Catholic Church among the indigenous people did not automatically displace long-established traditions; rather, it sought to build dialogue and openness through an inculturation approach. In this process, the Church endeavors to address local culture with the spirit of the Gospel, respecting local wisdom without sacrificing the truth of the Catholic faith. This paper highlights various forms of inculturation that have occurred, such as the use of local symbols in the liturgy, the involvement of traditional leaders in church activities, and spiritual dialogue that brings together customary values and the Gospel. Nevertheless, this process is not without its challenges, both theological and pastoral, particularly when certain customary elements conflict with the tenets of the faith. In this context, critical analysis and pastoral accompaniment are essential so that the custom and the Gospel can truly proceed hand-in-hand. The article concludes with a call for the Church to continue being present contextually and dialogically, enriching the faith life of the people without erasing their local cultural identity.